Answer:
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = -\frac{1}{8}[/tex]
Explanation:
Given
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9}[/tex]
Required
Solve
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9}[/tex]
Apply distributive property
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = \frac{9}{16}(\frac{4}{12}-\frac{5}{9})[/tex]
Solve the bracket
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = \frac{9}{16}(\frac{12 - 20}{36})[/tex]
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = \frac{9}{16}(\frac{-8}{36})\\[/tex]
Simplify
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = \frac{9}{16}(\frac{-2}{9})[/tex]
Open bracket
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = \frac{1}{16} * \frac{-2}{1}[/tex]
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = -\frac{2}{16}[/tex]
[tex]\frac{9}{16}*\frac{4}{12}+\frac{9}{16}*-\frac{5}{9} = -\frac{1}{8}[/tex]